Morphological and molecular characterization of Pratylenchoides persicus n. sp. (Nematoda: Merliniidae) and additional data on two other species of the genus from Iran - Azizi, Kourosh; Eskandari, Ali; Karegar, Akbar; Ghaderi, Reza; Elsen, Sven Van Den; Holterman, Martijn; Helder, Johannes (Zootaxa, 2016)
Some nematologists recently placed the genus Pratylenchoides, (“Lesion Nematode-like”) in the family Merliniidae. To investigate Pratylenchoides species diversity and their relationships with other Merliniidae genera, specimens were collected from various habitats in the northern and northwestern provinces of Iran. The morphological and molecular study yielded three species of the genus Pratylenchoides, including P. persicus n. sp. This new species is characterized by having lip region rounded or slightly flattened anteriorly with four or five fine but distinct annuli, pharyngeal glands off-set or slightly overlapping the intestine dorsally, all three gland nuclei located anterior to the pharyngo-intestinal valve and tail cylindrical with truncate to low rounded terminus. Morphologically, P. persicus n. sp. can be distinguished from the most closely related species, P. heathi by having shorter body and stylet length in females and males, as well as a shorter tail with different terminus in females. Pratylenchoides laticauda and P. cf. nevadensis are reported from Iran for the first time. Phylogenetic analysis based on the D2/D3 region of the large subunit of ribosomal DNA revealed Pratylenchoides as a monophyletic genus, and it supports the delineation of the new species, P. persicus n. sp.